Prevalence of stunting, thinness and anaemia among adolescents and their association with demographics and dietary habits - Kumari, Gudiya; Rathoria, Ekansh; Khan, Faraz Ahmad; Singh, Saurabh Kumar; Lahari, Rohitash; Rathoria, Richa; Bansal, Utkarsh; Singh, Amrita (International Journal of Contemporary Pediatrics, 2024)
Background: Adolescence marks the pinnacle of the nutritional need, therefore, it's crucial to detect undernutrition and anemia in adolescents before they exhibit adverse effects. To assess the prevalence of undernutrition and anemia among adolescents and their association with demographic factors and dietary habits. Methods: A cross-sectional study was conducted over 18 months at the Hind Institute of Medical Sciences, involving 250 adolescents aged 10-19 years. Data collection included anthropometric measurements, hemoglobin assessment, and a structured questionnaire capturing demographic characteristics and dietary habits. Statistical analysis (Descriptive statistics, Chi-square test) was performed using SPSS version 23.0. A p value <0.05 was considered significant. Results: The study found that 29.6% of adolescents were stunted, 27.6% were thin and 48% had anemia, with 11.6% classified as mild, 30% as moderate and 6.4% as severe anemia. No significant association was reported of stunting with demographic parameters. A significant association was found between thinness and joint family (p=0.044) but not with any other demographic parameter. An inverse relationship of Junk food intake with stunting (p<0.0001) and thinness (p<0.0001) was inferred. Anemia was found to be significantly associated with advancing adolescent age (p<0.0001), female gender (p<0.0001), nuclear family (p<0.0001), lower socioeconomic status (p=0.041), and vegetarian diet (p=0.009). Conclusions: The high prevalence of undernutrition and anemia among adolescents highlights the urgent need for targeted nutritional interventions. Regular anthropometric assessments and nutritional education programs are essential to address these health issues.